CHEMICAL AND BIOLOGICAL CHANGES IN KOMBUCHA FROM BLACK TEA, PINNEAPPLE AND MANGO - Milatina, Nada Ila; Khasanah, Aprilia Nur; Sari, Evida Agustina; Rokhmah, Laela Nur (LPPM Universitas Duta Bangsa Surakarta, 2025)
Kombucha is a beverage made by fermenting tea or fruit with added sugar and a scoby. A scoby (Symbiotic Culture of Bacteria and Yeast) is a starter that breaks down sugar into acetic acid and alcohol. This study used tea, Indramayu mango, and Honi pineapple. This study was conducted with observations on days 0, 7, and 14 by measuring pH, reducing sugar, alcohol, and scoby weight. The purpose of this study was to observe chemical and biological changes using different media. The results showed that fermentation occurred during this period. The longer the fermentation, the lower the pH level in all media and the sugar content also decreased. The longer the fermentation, the higher the alcohol content as a result of the fermentation process. The highest alcohol content was in pineapple kombucha with 3.25% on day 14. Increasing the fermentation time showed an increase in scoby weight. The results indicate that the media can be used as a kombucha medium. The fermentation time and sugar addition affect the quality of the final product.